Wave Impact Analysis on a Beach-Dune System to Support Coastal Management and Nourishment Works: The Showcase of Mira, Portugal - Fontán-Bouzas, Ángela; Andriolo, Umberto; Silva, Paulo A.; Baptista, Paulo (Frontiers in Marine Science, 2022)
At coasts, sandy beach-dune systems act as natural barriers to environmental forcing, preventing coastal flooding and protecting coastal communities. In the context of coastal studies, it is fundamental to identify beach-dune sectors exposed to wave impact to support coastal management and suggest soft engineering interventions. This work examines the morphodynamics of the Mira beach-dune system on the northern-central littoral of Portugal over the winter 2016-2017. Coupling topographic data with the estimation of wave runup and total water level (TWL) timeseries, we proposed an operational framework to spot the beach-dune system sectors most vulnerable to dune collision and overwash. The highest topographic variations occurred in the northern sector of the study area, where overwash events occurred due to low dune crest (DC) elevation. The dune toe (DT) was frequently collided by waves in the central sector, where the upper beach profile was the most variable during winter. Overall, wave collision and overwash events were registered not only during storms, but also during spring tides and mild wave conditions. Results highlight the importance of uploading the intertidal beach slope when computing the total water levels on wave-dominated mesotidal sandy beaches, and therefore, the need for a consistent monitoring program of the coastal zones. Findings of this work also supported the coastal management of beach-dune systems, where regional authorities need to restore dune ridges to prevent further overwash events and erosion. The presented framework can be applied to build a beach-dune system vulnerability map in response to wave forecast and predicted sea-level rise.